Quality control of the various orthosiphon stamineus leaf extracts using high‑performance liquid chromatography: Multivariate‑based and marker‑based analytical techniques - Ahda, Mustofa; Jaswir, Irwandi; Khatib, Alfi; Ahmed, Qamar Uddin; Mahfudh, Nurkhasanah; Prastowo, Indro; Rofiee, Mohd Salleh; Kashif, Mohammad; Samdani, Mohammad Shahzad (Springer Nature, 2025)
Ensuring herb quality is crucial for maintaining product consistency in herbal products. Marker-based analysis has traditionally been the preferred method for determining the chemical composition of medicinal plants due to its effectiveness. However, current challenges with marker-based analysis, such as high prices and difficulties in procurement, necessitate the application of multivariate-based approaches. Hence, this study aimed to compare marker-based and multivariate-based methods for quality control of an important plant used in traditional folk medicine, Orthosiphon stamineus leaf extracts. The results indicated that caffeic acid, chlorogenic acid, and rosmarinic acid are effective markers for classifying potent extracts. The aqueous extract of O. stamineus leaf was found to contain the highest concentration of caffeic acid (3.898 ± 0.098 μg/mg), while the 40% ethanolic extract exhibited the highest levels of rosmarinic acid (1.627 ± 0.026 μg/mg) and chlorogenic acid (4.258 ± 0.049 μg/mg). Additionally, the multivariate-based analysis yielded clear distinctions between O. stamineus leaf extracts. It has acceptable parameters as indicated by determination coefficients R2X: 0.917, R2Y: 0.957, and Q2Y: 0.92. Based on these findings, caffeic acid, chlorogenic acid, and rosmarinic acid can serve as specific markers for α-glucosidase inhibitors, with rosmarinic acid also serving as a specific marker for sLOX inhibitors. Therefore, chromatography-based analysis, whether through multivariate data analysis or marker-based approaches, can be applied effectively for quality control of the O. stamineus leaf extracts.